BUREAUCRATIZATION OF A REGIONAL UNIVERSITY - Valentin P. Babintsev (Высшее образование в России)
The key theme of the article is bureaucratization of scientific-educational environment of a regional university, which is considered as a process of socio-cultural changes, reflecting transformation of the subculture of bureaucracy into the cultural mainstream of Russian society. Consequences of bureaucracy for HPE institutions and the reaction of collectives of universities are analyzed.